2001
DOI: 10.1086/319157
|View full text |Cite
|
Sign up to set email alerts
|

[ITAL]Chandra[/ITAL] Observations of the X-Ray Jet of 3C 273

Abstract: We report results from Chandra observations of the X-ray jet of 3C 273 during the calibration phase in 2000 January. The zeroth-order images and spectra from two 40 ks exposures with the High-Energy Transmission Grating and Low-Energy Transmission Grating ϩ Advanced CCD Imaging Spectrometer-S show a complex Xray structure. The brightest optical knots are detected and resolved in the 0.2-8 keV energy band. The X-ray morphology tracks well the optical. However, while the X-ray brightness decreases along the jet,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
149
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(162 citation statements)
references
References 12 publications
13
149
0
Order By: Relevance
“…It is evident from the SEDs that the jet emission from radio up to X-rays cannot be explained as a single synchrotron component for any part of the jet. Except for region A, this was already known from the analysis of ROSAT data (Röser et al 2000) and of the first Chandra data sets (Marshall et al 2001;Sambruna et al 2001). Jester et al (2002 showed that a single-component synchrotron spectrum was not in fact viable for knot A, chiefly because the new multifrequency, multiconfiguration VLA data set used by them, and here, yielded substantially different radio SED shapes.…”
Section: Fit Results and Seds From Radio To X-raysmentioning
confidence: 56%
See 1 more Smart Citation
“…It is evident from the SEDs that the jet emission from radio up to X-rays cannot be explained as a single synchrotron component for any part of the jet. Except for region A, this was already known from the analysis of ROSAT data (Röser et al 2000) and of the first Chandra data sets (Marshall et al 2001;Sambruna et al 2001). Jester et al (2002 showed that a single-component synchrotron spectrum was not in fact viable for knot A, chiefly because the new multifrequency, multiconfiguration VLA data set used by them, and here, yielded substantially different radio SED shapes.…”
Section: Fit Results and Seds From Radio To X-raysmentioning
confidence: 56%
“…Regarding the SEDs, they came to conclusions similar to those by Röser et al (2000). Sambruna et al (2001) analyzed a smaller set of the early Chandra data and favored a beamed IC-CMB model for the emission from all parts of the jet. Marshall et al (2001) compared the optical and X-ray morphology at the Chandra resolution of 0B78 and found that the X-ray and optical emission come from the same parts of the jet and show very similar features.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the other LOS in the control model and the cooling model scatter The estimation of the local energy partitioning d based on B ic and B me works best in regions that are not strongly influenced by radiative aging and where the partitioning is not expected to vary strongly over short distances, such as inside jet structures. There is increasing evidence that the X-ray emission observed from some jets is Doppler-boosted IC/3K emission (e.g., Tavecchio et al 2000;Sambruna et al 2001;Celotti, Ghisellini, & Chiaberge 2001). In that case this kind of analysis could be useful still, but it would require taking beaming and boosting effects into account, which we have not done because the flows here are nonrelativistic.…”
Section: Comparison Between Inferred and Actual Energeticsmentioning
confidence: 99%
“…Since self-Compton scattering of the radio-optical emission can account only for a small fraction of the observed X-ray fluxes, Röser et al (2000) suggested to consider the X-rays as synchrotron emission from a second, higherenergy electron population. As an alternative, a contribution by beamed inverse Compton scattering of the cosmic microwave background has been suggested (Marshall et al 2001;Sambruna et al 2001). A distinction between these models is not possible based on the currently available X-ray data.…”
Section: Introductionmentioning
confidence: 99%